1996
DOI: 10.3178/jjshwr.9.489
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variation in Specific Discharge of Base Flow in a Small Catchments, Oe-Yama Region, Western Japan.

Abstract: Base flow from 66 tributaries in watersheds underlain by serpentinite , granite, and Paleozoic shale were measured in Oe yama region, Kyoto Prefecture, Western Japan. The base flow measurements sufficiently after rainfall were conducted during the snowmelt season (April) and summer dry season (August). Spatial variation of specific discharge was greater in the serpentinite basins than those in the granite and the Paleozoic shale basins . In addition, there are many tributaries without discharge in serpentinite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…In order to understand the water flow path at the scale of the entire watershed, i.e., both Y1 and Y2 or both K1 and K6, we observed the spring distribution and discharge (Onda, 1994;Komatsu and Onda, 1996). We monitored the spring distribution (Fig.…”
Section: Mountain-scale Water Flow Pathsmentioning
confidence: 99%
“…In order to understand the water flow path at the scale of the entire watershed, i.e., both Y1 and Y2 or both K1 and K6, we observed the spring distribution and discharge (Onda, 1994;Komatsu and Onda, 1996). We monitored the spring distribution (Fig.…”
Section: Mountain-scale Water Flow Pathsmentioning
confidence: 99%
“…Harr, 1977). However, recent field studies in forest soils show that preferential flow exuding from bedrock fractures can exert an important control on subsurface flux (Tsukamoto and Ohta, 1988;Hirose et al, 1994;Komatsu and Onda, 1996;Montgomery et al, 1997;Noguchi et al, 1999). Cleavage planes in bedrock may have similar influences.…”
Section: Preferential Flow Paths In Bedrock and Tillmentioning
confidence: 99%
“…Terajima et al (1993) monitored the water budget and runoff from a zero-order hollow and a first-order stream and concluded that bedrock percolation and bedrock outflow are evident in basins underlain by granitic rocks. The distribution of springs within basins during base flow was found to be a good indicator of subsurface water flow paths, in that regular distribution of many springs is believed to indicate soil water dominance and irregular or sparse spring distribution may indicate bedrock flow dominance (Onda, 1994;Komatsu and Onda, 1996).…”
Section: Introductionmentioning
confidence: 99%